Silver nanoparticles as a medical device in healthcare settings: a five-step approach for candidate screening of coating agents - Smith, Stephen; Volkov, Yuri; Prina Mello, Adriele (My University, 2018)
Silver nanoparticle-based antimicrobials can promote a long lasting bactericidal effect without detrimental toxic side effects. However, there is not a clear and complete protocol to define and relate the properties of the particles (size, shape, surface charge, ionic content) with their specific activity. In this paper, we propose an effective multi-step approach for the identification of a ‘purpose-specific active applicability window’ to maximize the antimicrobial activity of medical devices containing silver nanoparticles (Ag NPs) (such as surface coaters), minimizing any consequent risk for human health (safety by design strategy). The antimicrobial activity and the cellular toxicity of four types of Ag NPs, differing in their coating composition and concentration have been quantified. Through the implementation of flowfield flow fractionation, Ag NPs have been characterized in terms of metal release, size and shape. The particles are fractionated in the process while being left unmodified, allowing for the identification of biological particle-specific contribution. Toxicity and inflammatory response in vitro have been assessed on human skin models, while antimicrobial
PUBLISHED
Keywords: Silver nanoparticle-based; Silver nanoparticles; Healthcare; Coating agents; Hollow-fibre flow-field flow fractionation; Antimicrobials; Cellular toxicity